KAJIAN UNSUR - UNSUR TASAWUF DALAM NOVEL NEGERI 5 MENARA KARYA A. FUADI - Litra; Wardarita, Ratu (Universitas PGRI Palembang, 2022)
The method used is descriptive method. This research approach is based on a moral and didactic approach. The data source for this research is the novel Negeri5 Menara by A. Fuadi. PT Gramedia Pustaka Urama Published in 2009. Consists of 419 sections, 423 pages, book length 19.5 cm x width 13.7 cm. The data processing technology used is business analysis technology. The data collection stage consists of (1) data collection and data review, and (2) compiling the results of data inspection. Based on a study of elements of Sufism such as Tauba, Repentance, Patience, Fakr, Tawakal, Leda, Wala Talika, Dzat, Makriffat, Mahabba, Fana and Baka, Itihad and Hururu. As a result of the analysis, the study of elements of Sufism in the novel Negri 5 by Andy F. Noya includes Menara Tauba, Zuhad, Sabar, Faguk, Amanah, Redha, Wala, Tarika, Hakika and Makriffa. It can be concluded that there are several suggestions that the author gives, namely: (1) literary education in schools; The results of this study are expected to contribute to secondary school literature education, especially those related to elements of Sufism in novels. (2) Literature researchers are expected to be able to use the results of this research to conduct research other than library materials and comparisons. Provide input to study or examine literature from a different perspective.